The Influence of Intellectual Capital on Firm Value with Profitability as Moderating Variables in Real Estate & Property Companies Registered in Indonesia Stock Exchange, 2008-2018 - Novia Maheran; Azhar Maksum; Erwin Abubakar (Jurnal Mantik, 2021)
This study aims to determine and analyze the effect of intellectual capital on firm value with profitability as a moderating variable in real estate & property companies listed on BEI. The population of this study were 30 real estate & property companies listed on the Indonesia Stock Exchange in the period 2008 -2018.The samples were taken by applying saturated sampling technique or census sampling with a total of 330 observations. Data analysis method is secondary data using Eviews. The results of this study prove that simultaneously Intellectual Capital (VACA, VAHU and STVA) have a positive and significant effect on firm value, partially the VACA variable has a significant and significant effect on firm value while VAHU has a positive and insignificant effect and STVA has a negative and insignificant effect. on company value in real estate & property companies listed on the Indonesia Stock Exchange from 2008 to 2018. Meanwhile profitability was not significant in moderating VACA and VAHU, while Profitability was partially significant in moderating STVA to firm value